How do earthworms influence organic matter quantity and quality in tropical soils? - Hong, Hanh Nguyen; Rumpel, C.; Henry des Tureaux, Thierry; Bardoux, G.; Billou, D.; Tran Duc Toan; Jouquet, Pascal (Elsevier, 2011)
Earthworms are important regulators of soil structure and soil organic matter (SOM) dynamics; however, quantifying their influence on SOM cycling in tropical ecosystems remains little studied. Simulated rainfall was used to disrupt casts produced by Amynthas khami and their surrounding soil (control) into a range of small sized aggregates (50e250, 250e500, 500e2000 and 2000e5000 mm). To gain insight into how earthworms influence SOM biogeochemical composition in the aggregates, we carried out elemental and stable isotope analysis, and analytical pyrolysis (Py GC/MS). We also characterized their lignin component after oxidation with cupric oxide (CuO). The C content of smaller size fractions (<500 mm) in the control soil was higher than in the larger fractions. Our study therefore suggests that the aggregate hierarchy concept, which is used to understand soil aggregates and SOM dynamics in temperate soils, may not be applicable to the tropical Acrisol studied here. Earthworms modified SOM organization in soil aggregates. Although the isotope analyses were useful for highlighting SOM enrichment in the earthworm casts, aggregate fractions could not be classified according to particle size. Molecular analyses were necessary to indicate that SOM in all size fractions of casts consisted of relatively undecomposed material. Protection of the most labile SOM structures occurred in the smallest aggregate size fraction (50e250 mm). Py GC/MS showed that earthworm casts and control aggregates <2000 mm could be clearly distinguished according to the molecular properties of their SOM. Aggregates larger than 2000 mm, however, were most probably composed of all fractions and were not different. As a consequence, our results indicate that studies to determine the impact of earthworms on SOM turnover in soil are spatially dependant on the scale of observation.